Involvement of Charcot-Marie-Tooth disease gene mitofusin 2 expression in paclitaxel-induced mechanical allodynia in rats. (13th July 2017) - Yamashita, Yuta; Irie, Keiichi; Kochi, Akane; Kimura, Nami; Hayashi, Toshinobu; Matsuo, Koichi; Myose, Takayuki; Sano, Kazunori; Nakano, Takafumi; Takase, Yumi; Nakamura, Yoshihiko; Satho, Tomomitsu; et al.
Highlights: Paclitaxel induces mechanical allodynia but not cold hyperalgesia. Paclitaxel reduces expression of Mfn2 mRNA, but not Arhgef10 or Prx mRNAs. Paclitaxel reduces Mfn2 mRNA before the appearance of mechanical allodynia. Abstract: Paclitaxel induces peripheral neuropathy, which is dose-limiting and results in loss of quality of life. Therefore, the prevention and treatment of paclitaxel-induced peripheral neuropathy are major concerns in clinical cancer therapy. However, the detailed mechanisms have not been fully elucidated. It has recently been reported that allelic variability in the Charcot-Marie-Tooth disease (CMT) genes, mitofusin 2 ( MFN2 ), Rho guanine nucleotide exchange factor 10 ( ARHGEF10 ), and periaxin ( PRX ), affected paclitaxel-induced peripheral neuropathy in clinical cases. Therefore, we hypothesized that paclitaxel may induce peripheral neuropathy due to changes in Mfn2, Arhgef10, and Prx mRNA expression. Paclitaxel (6 mg/kg) was administered intraperitoneally, on two consecutive days per week for 4 weeks in rats. Paclitaxel-induced peripheral neuropathy was measured by the von Frey test and acetone test, mechanical allodynia, and cold hyperalgesia, respectively, on days 0, 3, 10, 17, and 24. Mfn2, Arhgef10, and Prx mRNA expression in the spinal cord were analyzed by qRT-PCR on days 3 and 24. Paclitaxel induced mechanical allodynia from days 17–24, but did not induce cold hyperalgesia. In addition, paclitaxel reduced Mfn2 mRNA expression, but not Arhgef10 or Prx mRNA expression, on days 3 and 24. In addition, Mfn2 mRNA level was decreased before the appearance of mechanical allodynia. The results of the present study suggest that a reduction in Mfn2 mRNA expression contributes to paclitaxel-induced mechanical allodynia.